PEMBESARAN IKAN KERAPU BEBEK - Cromileptes altivelis (VELENCIENNES, 1828) DAN IKAN KERAPU LUMPUR - Epinephelus coioides (HAMILTON, 1822) PADA KERAMBA JARING APUNG (KJA) - Langkosono, Langkosono (BERITA BIOLOGI, 2005)
Study on the fish rearing of the grouper (Serranidae) as well as barramundi cod grouper - C. altivelis (Valenciennes, 1828) and green grouper - E.coioides (Hamilton, 1822) in floating net cages was carried out from June to December 2004 at the coastal waters of Kodek Bay, Malaka Village, Pemenang District West Nusa Tenggara. This paper discussed the results of both grouper fishes grown in Floating Net Cages culture.